An Eco‐Friendly Enantioselective Access to (R)‐Naringenin as Inhibitor of Proinflammatory Cytokine Release. Issue 8 (12th August 2013) - Gaggeri, Raffaella; Rossi, Daniela; Daglia, Maria; Leoni, Flavio; Avanzini, Maria Antonia; Mantelli, Melissa; Juza, Markus; Collina, Simona
Abstract (RS)‐Naringenin is a flavanone well‐known for its beneficial health‐related properties, such as its anti‐inflammatory activity. The preparative enantioselective chromatographic resolution of commercial (RS)‐naringenin was performed on a Chiralpak AD‐H column (500×50 mm i.d., dp 20 μm) using MeOH as eluent. The developed method is in accordance with the principles of green chemistry, since the environmental impact was lowered by recycling of the eluent, and allowed the production of gram amounts of each enantiomer with high purity (chemical purity >99%, enantiomeric excess (ee) >94%). Racemic and enantiomeric naringenin were subjected to an exhaustive in vitro investigation of anti‐inflammatory activity, aimed at evaluating the relevance of chirality. The assay with cultured human peripheral blood mononuclear cells (hPBMC) activated by phytohemagglutinin A revealed that (R)‐naringenin was more effective in inhibiting T‐cell proliferation than the (S)‐enantiomer and the racemate. Moreover, (R)‐naringenin significantly reduced proinflammatory cytokine levels such as those of TNF‐α and, with less potency, IL‐6. These results evidenced the anti‐inflammatory potential of naringenin and the higher capacity of (R)‐naringenin to inhibit both in vitro hPBMC proliferation and cytokine secretion at non toxic doses. Thus, (R)‐naringenin is a promising candidate for in vivo investigation.